Stock Market Mispricing: Money Illusion or Resale Option? - Chen, Carl R.; Lung, Peter P.; Wang, F. Albert (Journal of Financial and Quantitative Analysis, 2009)
Abstract We examine two hypotheses to explain stock mispricing: i) the money illusion hypothesis (Modigliani and Cohn (1979)) and ii) the resale option hypothesis (Scheinkman and Xiong (2003)). We find that the money illusion hypothesis may explain the level, but not the volatility, of mispricing in the U.S. market. In contrast, the stock resale option hypothesis, which stems from heterogeneous beliefs about future dividend growth rates and short-sale constraints, can explain both the level and the volatility of mispricing. The evidence suggests that while the two hypotheses complement each other in explaining the level of mispricing, the resale option hypothesis provides a more coherent explanation for asset price bubbles, in which extraordinarily high price levels are often accompanied by excessive volatility and frenzied trading.